The Use Of International Experience In The Framework Of Skill Enhancement Course For Unesco Aspnet Educators - A. Belyaeva, Evguenia (2019)
The relevance of the present issue is caused by a strong need to adapt educational curriculum of teacher training courses to the requirements of ever-more connected world and emerging of Knowledge Societies for fostering quality education and global citizenship principles at regional, national and international levels. The aim of the study is to demonstrate the pedagogical and humanitarian potential of adding UNESCO global agenda issues into career development programs for teaching staff on the example of successfully completed release of training course in Kazan, Russia. The key research method used within empirical approach was the study of the educational structure activity (extended courses “UNESCO ASPnet teacher”), monitoring of training materials and pedagogical observation. The research resulted in the conclusion that addressing global social, cultural, and educational issues is extremely beneficial to students and practicing teachers, providing the formation of a new outlook and understanding of global coherence and responsibility, boosting their personal and professional development. The article is of practical interest for acting and potential project participants, instructors and managers from secondary comprehensive, vocational, tertiary and extended educational institutions.